The computer - Oxlade, Chris (Chicago, Ill Heinemann Library, 2011)
Starting out as a machine so large it needed its own room and evolving to a machine that fits in our palms, the computer has come a long way in a relatively short time. This book tells the story of the invention of the computer, including the key players, setbacks along the way, and moments of discovery
A gift from book Africa
Computer
1 2 13 15
Keywords: Computers; Computers -- Juvenile literature